TRIPS waiver decision for equitable access to medical countermeasures in the pandemic: COVID-19 diagnostics and therapeutics - Nirmalya Syam; Muhammad Zaheer Abbas (South Centre, 2024)
The Marrakesh Agreement Establishing the World Trade Organization (WTO) allows WTO Members to agree to temporarily waive obligations under the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement). However, the TRIPS Decision adopted by the 12th WTO Ministerial Conference in June 2022, after lengthy and protracted negotiations lasting for 20 months in the middle of a pandemic, allowed only a fragment of the waiver proposal submitted by India and South Africa. Moreover, since the adoption of the Decision there has been an impasse in the WTO about extending the Decision to COVID-19 diagnostics and therapeutics even though the WTO Members were mandated by the Decision to decide on this matter within six months of the Decision. This research paper analyses the current state of play and concludes that there is a need to immediately and unconditionally extend the Decision to COVID-19 diagnostics and therapeutics. Moreover, the paper suggests options for how the TRIPS flexibilities can be optimally utilized in a pandemic situation without developing countries being resigned to the vagaries of negotiations on a waiver which is supposed to be an urgent emergency solution. In this regard, the paper also suggests options that could be considered for reforming the process of decision-making on a waiver proposal to ensure that decisions on waivers are taken in a timely and expedited manner without being negotiated for an extensive period of time in the midst of an emergency.
Keywords: 300; Coronavirus; Medizinische Behandlung; TRIPS; WTO-Recht; Welt